(3efXheI aj GdCjGe GdJi jUM ChdG jUM ajgG GdefGes - (3eMeO GdSeGhj , eMeO Hf WGgQ GdSeGhj,J (B1370 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO aGdCMdGe ai GdefGe jUOb HYVgG dOi CjGe hHYVgG jUOb ai GdJCNjQ hHYVgG jUOb HGdSQhQ s
(3BNQgG (B:s
(3HeG jUM ChHeG djS jUM ef Mde ai cd jhe bO TQM aGdMeO ddg Ydi GdEJeGe Ke GdKfG dKahI GdCfGe s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3JYHjQ GdQDjGs